Management of Abnormal Cervical Cytology: Atypical Squamous Cells of Undetermined Significance (ASC-US) and Atypical Squamous Cells cannot exclude High Grade Intraepithelial Lesion (ASC-H) - Kusuma, Fitriyadi; Liedapraja, Mediana s. (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To review for the management of abnormal cervical cytology: atypical squamous cells of undetermined significance (ASCUS) and atypical squamous cells cannot exclude high-grade intraepithelial lesion (ASC-H) as a treatment of cervical precancerous lesions in order to avoidexcessive treatment, reduce of unnecessary examinations and to provide cost effectively. Method: Literature study on published literatures and studies about the management of cervical cytology. Conclusion: The results of ASC-US cervical cytology and ASC-H is aninitial screening to detect precancerous cervical lesions. Definitive therapy should be done when finding a low-grade lesions (LSIL) and high degree of lesion(HSIL) squamous intraepithelial. A clinician expected to understand the natural history of HPV infection and the management of precancerous cervical lesions properly. [Indones J Obstet Gynecol 2013; 37-3: 166-170] Keywords: ASC-H, ASC-US, cervical cytology abnormalities, cervical precancerous lesion.